Hieracium sudetotubulosum (Asteraceae), a new name for the illegitimate H. tubulosum (Tausch) Tausch - Szelag, Zbigniew (Phytotaxa, 2014)
Hieracium alpinum var. tubulosum Tausch (1828: 63) was raised to species rank as H. tubulosum (Tausch) Tausch (1837: 68), an illegitimate homonym of H. tubulosum Lamarck (1786: 367). The latter is a different, unrelated species pertaining to the H. intybaceum aggregate and described from the Alps, whereas Tausch’s taxon is endemic to the Sudetes and belongs to the H. alpinum aggregate (Chrtek, 1997). Hieracium tubulosum (Tausch) Tausch differs from other central European species of the H. alpinum aggregate by having tubular florets, so that the replacement name proposed below is etymologically appropriate.